Wear mechanism investigation in a centrifugal slurry pump impeller by numerical simulation and experiments. (October 2021) - Peng, Guangjie; Chen, Qiang; Bai, Ling; Hu, Ziqiang; Zhou, Ling; Huang, Xin
Highlights: Wear mechanism in the impeller was investigated numerically and experimentally. The solid slip velocity is one of the key factors to identify the wear location. The wear location predicted by the simulations agreed well with experimental observations. Abstract: Centrifugal slurry pumps are widely used in ore mining, metal smelting, petrochemical and other industries. They are mainly used to transport muddy fluids containing a large number of solid particles. The impellers in slurry pumps always experience serious wear with damages the equipment. This study analyzed the flow in a slurry pump to identify the key sources of the wear. A centrifugal slurry pump was analyzed using the particle Eulerian-Eulerian multiphase flow model to study the impeller wear. The results show that increasing the flow rate causes the high solid volume fraction area to gradually move along the suction surface from the inlet to the outlet. At over-load flow rate, the high volume fraction area moves to the junction of the blade and the rear shroud. For the same conditions, increasing the concentration reduces the pump lift and efficiency, gradually increases the solid slip velocity at the blade outlet, and creates higher solid volume fractions on the suction surface of the blade than that on the pressure surface. The wear location predicted by the simulations agreed well with experimental observations. This study provides guidance on how to optimize slurry pump impeller designs to reduce the wear.